TEACHING GRAMMAR RULES IN PRACTICAL SPEECH - Almatova Nodira Anvar qizi; Umirzaqova Iroda Yunus qizi; Muhammadiyeva Mahliyo Ravshan qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
ANNOTATION The article examines methods of teaching English grammar rules in practical speech. It highlights the importance of applying grammar in real communicative contexts rather than just learning rules theoretically. The study discusses common errors made by students in speech, their causes, and effective strategies for correcting them. Pedagogical approaches such as role-plays, dialogues, interactive exercises, and error analysis are emphasized. The research demonstrates that teaching grammar through practical speech enhances students’ communicative competence, encourages independent learning, and increases motivation.